Transformation, Dialogue and Collaboration: Developing Studio-based Concept Writing in Art and Design through Embedded Interventions - Thomas, Peter (Journal of Academic Writing, 2013)
This article analyses two examples of embedded academic writing and language provision within Art and Design (A&D) degree programmes in Animation and Fashion Textiles. The provision took the form of interventions to develop the students’ writing as part of their studio practice, specifically to help them generate concepts and develop studio-based design work. As such, the writing in these interventions formed part of a repertoire of strategies or tools for the development of design, and so was not focused on traditional academic writing (in the form of essays). The interventions were the product of close collaboration with specialist lecturers from the degree courses and were co-taught with them. We drew on practices and priorities from the studio disciplines and were informed by broadly Academic Literacies and Critical Pedagogy approaches, as well as ideas from Bakhtin (1981) and Freire (1996) on dialogue, and Medway (1996) on writing in art and design. This article finds that in terms of engagement and confidence with studio-based writing, the interventions had a transformative impact on the students. It also finds that where the interventions were most successful, dialogue played a number of key roles. The paper highlights the value of working on a form of studio-writing that is relatively unexamined; the transformative potential of embedded work like this; and the benefits of dialogue and collaboration inherent in this kind of intervention.